Deficiency of germinal center kinase TRAF2 and NCK-interacting kinase (TNIK) in B cells does not affect atherosclerosis - van Os, Bram W.; Kusters, Pascal J. H.; den Toom, Myrthe; Beckers, Linda; van Tiel, Claudia M.; Vos, Winnie G.; de Jong, Elize; Kieser, Arnd; van Roomen, Cindy; Binder, Christoph J.; Reiche, Myrthe E.; de Winther, Menno P.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Atherosclerosis is the underlying cause of many cardiovascular diseases, such as myocardial infarction or stroke. B cells, and their production of pro- and anti-atherogenic antibodies, play an important role in atherosclerosis. In B cells, TRAF2 and NCK-interacting Kinase (TNIK), a germinal center kinase, was shown to bind to TNF-receptor associated factor 6 (TRAF6), and to be involved in JNK and NF-κB signaling in human B cells, a pathway associated with antibody production. Objective We here investigate the role of TNIK-deficient B cells in atherosclerosis. Results ApoE−/−TNIKfl/fl (TNIKBWT) and ApoE−/−TNIKfl/flCD19-cre (TNIKBKO) mice received a high cholesterol diet for 10 weeks. Atherosclerotic plaque area did not differ between TNIKBKO and TNIKBWT mice, nor was there any difference in plaque necrotic core, macrophage, T cell, α-SMA and collagen content. B1 and B2 cell numbers did not change in TNIKBKO mice, and marginal zone, follicular or germinal center B cells were unaffected. Total IgM and IgG levels, as well as oxidation specific epitope (OSE) IgM and IgG levels, did not change in absence of B cell TNIK. In contrast, plasma IgA levels were decreased in TNIKBKO mice, whereas the number of IgA+ B cells in intestinal Peyer's patches increased. No effects could be detected on T cell or myeloid cell numbers or subsets. Conclusion We here conclude that in hyperlipidemic ApoE−/− mice, B cell specific TNIK deficiency does not affect atherosclerosis.